Morfología del gametófito de cuatro subespecies de Asplenim trichomanes L. - Prada Moral, Carmen; Pangua, Emilia; Rubio Sánchez, Agustín; Herrero, Alberto; Escudero, Adrián; Pajarón Sotomayor, Santiago (Botanica Complutensis, 1993)
HI?RREito, A., PL